Clinical status and cytokine profiles in patients with asthma or chronic obstructive pulmonary disease vaccinated against influenza - Mikhail Kostinov; Alexander Chuchalin; Anna Chebykina; Isabella Khrapunova; Alexander Cherdantsev; Irina Solov’eva; Nelli Akhmatova; Valentina Polishchuk; Nadezhda Kryukova; Aristitsa Kostinova; Anna Vlasenko; Marina Loktionova; et al. (PLoS ONE, 2025)
Background Influenza vaccine is a tool for preventing infection and reducing exacerbations in patients with asthma and chronic obstructive pulmonary disease (COPD). However, the associations between clinical outcomes and changes in the levels of inflammation markers have not been fully delineated. The purpose of this study was to investigate the clinical course and the changes in the levels of inflammation markers in patients with asthma or chronic obstructive pulmonary disease for one year after vaccination against influenza. Methods The prospective study for one year included 34 patients with asthma, 20 patients with COPD vaccinated against influenza, both groups being under a basic maintenance therapy, and 26 healthy individuals vaccinated with the trivalent polymer-subunit (adjuvanted) vaccine, containing 5 μg of influenza virus strains and 500 μg of azoximer bromide. The levels of C-reactive protein (CRP) and serum cytokines (IL-2, IL-6, IL-10, and IL-17) were measured by enzyme-linked immunosorbent assay (ELISA) at baseline and 6 and 12 months after vaccination. Results Over a year after vaccination against influenza, the frequency and duration of bronchopulmonary exacerbations significantly decreased both in patients with asthma and those with COPD: by 1.9–2 and 2.2–2.5 times, respectively. There was also a significant reduction in the frequency and duration of hospitalization (by 2.0–2.5 and 2.3–3 times, respectively). Other changes observed over the one-year follow-up period included a 1.6-fold reduction (р<0.01) in the need for outpatient care and a reduction in the number of courses of systemic corticosteroids (by 16.7%; р<0.05) in asthma patients; and a 3.6-fold decrease (р<0.05) in the number of courses of antibiotics in COPD patients. Twelve months after vaccination against influenza, the study participants had significantly lower IL-6 levels, and COPD patients, additionally, showed a reduction in IL-10 levels compared to baseline. Our study identified certain correlations between positive clinical outcomes of vaccination and levels of inflammation markers. Discussion Analysis of the immunological, clinical and functional parameters in asthma and COPD patients showed that vaccination not only reduces the risk of influenza and other respiratory infections due to activation of non-specific protection, but also improves the clinical course of asthma and COPD.